Epidemiological determinants of psoriasis - Islam, MT; Paul, HK; Zakaria, SM; Islam, MM; Shafiquzzaman, M (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):9-15 The abstract of this article is available on the PubMed website